Integrated control of braking and steering for vehicle stability considering the parametric uncertainties and input constraints. (3rd March 2009) - Yang, Xiujian; Wang, Zengcai
A vehicle dynamics controller is designed to improve vehicle handling and stability by coordinating Active Front Steering (AFS) and differential braking with the consideration of input constraints. An uncertain integrated control model is constructed by choosing the tyre cornering stiffness and longitudinal velocity as the uncertainties. A state feedback integrated controller based on Optimal Guaranteed Cost with input Constraints (OGCC) is developed which can not only attenuate the influence of the modelling uncertainties on vehicle dynamics but also reduce the possibility of actuators' saturation. Simulations on an 8-DOF nonlinear vehicle model demonstrate the satisfying performance of the OGCC scheme.